(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The paper is devoted to the methodological foundations of intensive training in oral professional speech and peculiarities of forming English language competence of students of choreographic faculty. The expediency of adaptation of principles of communicative-cognitive approach to the learning environment of future choreographers to the conditions of teaching English for professional communication and identifies the methodological principles of forming English language linguistic competence of students. Considered a modern technology in teaching English in high school. Modern technology in education this professionally-oriented foreign language teaching, project work in teaching, application of information and telecommunication technologies, work with computer training programs in foreign languages (multimedia system), e-learning technologies in teaching foreign languages, creating presentations in PowerPoint, using Internet resources, learning foreign language in a computer environment (forums, blogs, e-mail), newest testing technologies (the creation of a Bank of diagnostic materials in the course of academic subject «Foreign language» for computer-based testing to control students). Methodical peculiarities of forming English language linguistic competence in oral speech of students of choreographic faculty due to the adaptation of the principles of communicative-cognitive approach to the learning environment of English for professional communication. The paper shows the methodical features, which include: the perspective of the needs of the communicative activity of the future choreographers; multi-level approach to teaching oral speech; adherence to the principles of interdisciplinarity. Methodical features of formation of linguistic competence in English speech of students of choreographic faculty due to the adaptation of the principles of cognitive-communicative approach to English learning environment for professional communication. Identified methodological features, including: consideration of future needs of communication of future choreographers; build a course around the subject matter and pragmatic-communicative functions of professional communication; multi-tiered approach to the study of speech; adherence to the principles of interdisciplinarity, intensive use of background knowledge, development and improvement of all aspects of secondary verbal identity, authenticity, interactivity, contextual conditioning, cognitive gap.